Analysis Of Competitive Strategies At The Santika Premier Dyandra Hotel Medan In Facing Competition In The Hotel Industry In The City Of Medan - Ramadhani , Liska; Wulandari Lubis, Dewi Shinta (SEAN Institute, 2024)
Hotels are a service sector that offers services, such as overnight services, front office, food and beverage, and also recreation. It is know that the number of hotels has increased significantly in the 2021-2023 priode. this research aims to determine the development of competition in the hotel industry at the santika premiere dyandra medan petisah, medan city, north sumatera. This research uses qualitative methods with in-depth interview participant observation. The result of this research at the santika premiere dyandra hotel medan in facing competition in the hotel industry in the city of medan and a sales marketing has carried out their responsibilities and their job desk well and always provides profesional direction,carrying out B2B (business to business) B2C (Business to Customers) marketing, maake sales calls, sales visit, promotion and events. All front office Departements always apply the characteristics of service dimensions,,namely is tangible, reliability, responsiveness,assurance and emphaty.